Sidewall surface roughness of Sputtered Silicon 1: surface modelling - Ali, Mohammad Yeakub; Hung, N. P.; Ngoi, B. K. A.; Yuan, S. (Maney Publishing, 2003)
Mathematical models for the calculation of sidewall surface roughness have been developed for focused ion beam (FIB) sputtering. The surface roughness profile at the sidewall was different to the bottom surface profile for the same sputtering parameters and substrate material. The cumulative sputtering by the Gaussian beam creates a steady state surface profile at the sidewall which has been used to develop surface roughness models. The ion intensity distribution profile was considered to be Gaussian. The beam function includes ion type, ion acceleration voltage, beam radius, tailing and neighbouring of the successive beams. Knowing the beam radius and pixel spacing, sidewall surface roughness of FIB sputtered microfeatures can be calculated using these models. The substrate material function has no direct effect on the sidewall surface profile if the same material is used for the study of beam profile and fabrication of microfeatures.